2020
DOI: 10.5400/jts.2020.v25i2.83-92
|View full text |Cite
|
Sign up to set email alerts
|

Vermicast of Earthworm as Ecosystem Engineers within Different Vermireactor Shape

Abstract: Earthworms as ecosystem engineers can modify the quality of vermibed assembled from mixed soil with organic material in a vermireactor. Various in shapes of the vermireactor are used to produce a vermicast for biofertilizer in agriculture. The objective of this research was to study the vermicast production and its quality produced from a variety of vermireactor shapes. Earthworm (Pheretima sp.) which was applied to the vermireactor consists of: with- and without of earthworms. Three shapes of the vermireactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…could survive in soil contaminated with agricultural chemicals (Goto and Sudo, 2018) and Pb/Zn mine tailings (Cheng and Wong, 2008). Previously, Kilowasid et al (2020) reported the species could be mixed with soil and compost from "komba-komba" (Chromolaena odorata L.) pruning engineered to be about 49.24% cast, which contains various morphological types of bacterial. Although Pheretima sp.…”
Section: Introductionmentioning
confidence: 99%
“…could survive in soil contaminated with agricultural chemicals (Goto and Sudo, 2018) and Pb/Zn mine tailings (Cheng and Wong, 2008). Previously, Kilowasid et al (2020) reported the species could be mixed with soil and compost from "komba-komba" (Chromolaena odorata L.) pruning engineered to be about 49.24% cast, which contains various morphological types of bacterial. Although Pheretima sp.…”
Section: Introductionmentioning
confidence: 99%
“…The spore morphology of AMF at 400 times magnification using a light microscope were identified in line with a previous study [18]. Soil composite from each treatment after 8 weeks was analyzed for the following chemical character: pH H2O (1:2.5) with pH meter, C-organic with organic carbon reduced under acid condition, color intensity formed due to Cr 6+ reduction to Cr 3+ measured using a spectrophotometer at 561 nm wavelength, total N with Kjeldahl method, the intensity of indophenol blue color measured using a spectrophotometer at 636 nm wavelength, total P with an extract of HCl 25N, and intensity of blue color formed due to P-reagent staining measured using a spectrophotometer at 889 nm wavelength [19]. The values of each character listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Limbah organik yang dihasilkan dari aktivitas pertanian, pengrajin mebel/sawmill, dan rumah tangga di wilayah Kelurahan Mokoau merupakan sumber bahan baku utama pembuatan biofertilizer nonmikroba, seperti biochar untuk pembenah kualitas tanah dan kompos sebagai pupuk organik untuk mengembalikan hara yang tersimpan dalam bahan organik ke dalam tanah dan pemulihan kualitas tanah kebun petani. Urine dari kandang sapi warga, limbah cair rumah tangga seperti air cucian beras, dan lindi kompos (compost tea) dapat digunakan sebagai pupuk organik cair dan larutan pembawa mikroba lokal dekomposer (MOL) dalam proses pembuatan kompos (Fermin et al 2020;Kilowasid et al 2020).…”
Section: Pendahuluanunclassified